2019
DOI: 10.1186/s41239-019-0139-0
|View full text |Cite
|
Sign up to set email alerts
|

What foresees college students’ tendency to use facebook for diverse educational purposes?

Abstract: The present study investigates some factors affecting college students' tendency to use Facebook for different educational purposes. We reached 120 participants who were college students. Our sample comprised of 63 (52.5%) females and 57 (47.5%) males. We applied convenience sampling technique and an online questionnaire to collect data. Descriptive statistics, multiple regression analysis, and Structural Equation Modelling using IBM SPSS AMOS were utilized. The findings provide that GPA, Personal Use of Faceb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 72 publications
(95 reference statements)
0
43
0
Order By: Relevance
“…In addition, Facebook allow its users to utilize several interesting features in order to perform numerous activities and tasks such as creating personal profile for presenting themselves to others, nurturing existing relationships (friends, family members, coworkers, and acquaintances), uploading pictures and videos, posting status updates, expressing personal opinions and views in writing or through live streaming, establishing new relationships, creating Facebook pages/ groups representing public figures, institutions, organizations, businesses, brands or products and other entities (Cheung et al, 2011;Junco, 2015;Thompson & Lougheed, 2012;Tsay-Vogel, Shanahan, & Signorielli, 2016;Valkenburg et al, 2017). The purpose of Facebook adoption and usage differs greatly depending on users' interests, priorities, affiliations, attitudes and perceptions (Brailovskaia & Bierhoff, 2016;Hayes et al, 2015;Junco, 2015;Kuzma & Wright, 2013;Toker & Baturay, 2019;Wandeep et al, 2019).…”
Section: Facebook Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Facebook allow its users to utilize several interesting features in order to perform numerous activities and tasks such as creating personal profile for presenting themselves to others, nurturing existing relationships (friends, family members, coworkers, and acquaintances), uploading pictures and videos, posting status updates, expressing personal opinions and views in writing or through live streaming, establishing new relationships, creating Facebook pages/ groups representing public figures, institutions, organizations, businesses, brands or products and other entities (Cheung et al, 2011;Junco, 2015;Thompson & Lougheed, 2012;Tsay-Vogel, Shanahan, & Signorielli, 2016;Valkenburg et al, 2017). The purpose of Facebook adoption and usage differs greatly depending on users' interests, priorities, affiliations, attitudes and perceptions (Brailovskaia & Bierhoff, 2016;Hayes et al, 2015;Junco, 2015;Kuzma & Wright, 2013;Toker & Baturay, 2019;Wandeep et al, 2019).…”
Section: Facebook Literature Reviewmentioning
confidence: 99%
“…Even though, Facebook platform offer tremendous educational potentials, Facebook has been extensively utilized for social activities (interaction with each other based on shared interests, backgrounds or characteristics) rather than using it as a substitute for educational purposes. However, the growing popularity of Facebook based social networking among college/university students across the globe has led social media communication researchers and educators to investigate and identify several determinants that may motivate and attract the students to embrace Facebook in educational contexts or to highlight its potential influences on students' non-academic and academic outcomes (Dabner, 2012;Toker & Baturay, 2019).…”
Section: Facebook Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…It is followed by Spanish (310 million), Indonesian (170 million), Arabic (150 million) and Portuguese (150 million) as the languages most used on Facebook after English (Badache, 2019). Facebook has been used for an educational purpose that can accommodate communications, interaction with peers, collaborations and classroom exercises (Toker & Baturay, 2019). However, excessive Facebook use was argued to interfere with students` studying (Toker & Baturay, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…College students are an important user group of Facebook. Most college students have a Facebook account and they are also major users of Stories [ 12 ]. Bayer et al’s study observed that college students have a preference for ephemeral forms of social media [ 1 ].…”
Section: Introductionmentioning
confidence: 99%